Polska literatura Zagłady. Odsłona pierwsza: 1939-1968 - Kuczyńska-Koschany, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The text is a critical attempt discussing the compendium Literatura polska wobec Zagłady, (“Polish Literature in the Face of the Holocaust”) edited and published by three prominent scholarly experts on the subject: Sławomir Buryła, Dorota Krawczyńska and Jacek Leociak. This is the first of the three volumes of the series Reprezentacje Zagłady w kulturze polskiej (“Representations of the Holocaust in Polish Culture”) – an endeavour which is imposing already in its first instalment concerning the years 1939-1968. The time frame of the abovementioned volume is marked by the date of the beginning of World War II (1939), resulting in the Holocaust of the Jews of Europe, and a “dry pogrom”, that is was the anti-Semitic campaign in Poland in 1968 (the campaign itself and its writings shall be examined in the following volume). A comprehensive and very carefully prepared monograph has been divided into two fundamental parts: concerning the literature reacting to the Holocaust conducted by Nazi Germany during the war (1939-1945) and discussing the literary echoes of that genocide in the years 1945-1968. The study and invaluable interpretational effort have been focused on personal document literature (Marta Janczewska, Jacek Leociak), the prose (Sławomir Buryła, Dorota Krawczyńska), the poetry (Piotr Matywiecki) and the press (Ewa Koźmińska-Frejlak). A separate chapter has been devoted to a the “global text”, i.e., Archiwum Ringelbluma (“Ringelblum’s Archives”). Highly appreciating the entire volume as well as its individual fragments, recalling fundamental considerations and the ones concerning details, finally, proposing small corrections and pointing to minor shortcomings, the author of the critical review suggests the use of the formula “Polish literature of the Holocaust” (analogous to the formula coined by Grzegorz Niziołek “Polish theatre of the Holocaust”) as the one principally necessary to be contrasted with the formula “Polish literature of war and occupation”.